Family planning KAP survey in the Southern Region of Saudi Arabia - Dhaher, Enas A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Family planning practices could be determined through adopting proper knowledge and positive couple attitudes towards the use of family planning which would most likely result in favourable family decisions which would benefitted both the individual and the overall country welfare. Methods: A cross sectional study has been conducted using a structured questionnaire administered through face-to-face interview to a convenient sample of 151 pregnant women attending the obstetrics and gynaecology outpatient clinic at the Armed Forces Hospital in the southern region of Saudi Arabia in December 2014. Results: The results revealed that modern methods were popular among women. In general we found positive attitudes towards family planning among the sampled women as two third of the women have ever used contraceptives. However, the present study showed that 34% of women had unmet need of family planning. Women’s age, marriage years and number of children were all found to be associated factors with unmet need. Conclusions: National organized family planning programs might help satisfying the family planning needs for the families. Further studies regarding southern men’s knowledge and attitudes towards family planning is recommended.